Peran Komunikasi Efektif dalam Meningkatkan Kolaborasi antara Manajemen Pendidik dan Tenaga Kependidikan SMPN 40 Surabaya - Oktarina, Risma Putri; Zeniarda, Salma Eka; Windasari, Windasari (TSAQOFAH, 2024)
Building an effective communication system in the educational sector or institution is a way that an educational organization/institution can respond to global challenges so that it is able to produce appropriate expectations. Effective communication between educational management and educational staff is the most important part of the supervision process in the educational sector which moves education to become more interactive, collaborative and able to be oriented towards achieving learning goals. What will be achieved in this research is analyzing the role of effective communication in supervision or educational institutions and also emphasizing the concept of the importance of effective communication in order to improve the cooperative attitude and performance of educational staff. The method used in this writing is through interviews, observation, data analysis from observations and interviews, collecting and reviewing relevant literature published in the form of scientific works that are appropriate to the topic of this research. The results of this research show that effective communication plays a very important and necessary role because it is crucial in building an attitude of cooperation, providing facilities for the exchange of performance and experience and input of brilliant ideas can also increase the quality of supervision from supervision, providing constructive feedback can also be achieved. provide solutions to problems of opinion in the field of education. Effective communication in the field of education can strengthen a sense of connection and also help develop the professional attitudes of education staff.